(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
Linguodidactic innovations of the 21st century have become an integral part of the modern educational process. The development of technologies and teaching methods, as well as the introduction of new pedagogical approaches into linguodidactics, have significantly changed the ways of teaching foreign languages. Modern teaching methods, such as the use of information and communication technologies (ICT), interactive methods, and digital platforms, make the learning process more effective and accessible. This article discusses the main linguodidactic innovations and their impact on the educational process and teacher training.